Characterization of approximate Decentralized Fixed Modes in terms of DFM radius - Sahoo P.R.; Ghosh S.; Naskar A.K. (My University, 2025)
It is well known that the Decentralized Fixed Mode (DFM) are fixed w.r.t of Linear time-invariant (LTI) decentralized controller. But some modes which are very close to DFM but not exact DFM are called as approximate DFM (ADFM) and a huge control energy is required to shift these modes to a desirable region in complex plane which is not realizable practically. So characterization and determination of these modes are necessary. In this paper, a new quantitative characterization technique of ADFM is proposed by using fixed mode (FM) radius and old characterization techniques are reviewed. ADFM is computed by using proposed method with the help of some numerical examples. © 2017 IEEE.